A simple classification of pancreatic duct size and texture predicts postoperative pancreatic fistula: a classification of the International Study Group of Pancreatic Surgery - Schuh, Fabian; Mihaljevic, André L.; Probst, Pascal; Trudeau, Maxwell T.; Müller, Philip C.; Marchegiani, Giovanni; Besselink, Marc G.; Uzunoglu, Faik; Izbicki, Jakob R.; Falconi, Massimo; Castillo, Carlos Fernandez-del; Adham, Mustapha; et al. (Annals of surgery, 2023)
Objective: - The aim of this study was to develop a classification system for pancreas-associated risk factors in pancreatoduodenectomy (PD). - Summary Background Data: - Postoperative pancreatic fistula (POPF) is the most relevant PD-associated complication. A simple standardized surgical reporting system based on pancreas-associated risk factors is lacking. - Methods: - A systematic literature search was conducted to identify studies investigating clinically relevant (CR) POPF (CR-POPF) and pancreas-associated risk factors after PD. A meta-analysis of CR-POPF rate for texture of the pancreas (soft vs not-soft) and main pancreatic duct (MPD) diameter was performed using the Mantel-Haenszel method. Based on the results, the International Study Group of Pancreatic Surgery (ISGPS) proposes the following classification: A, not-soft (hard) texture and MPD >3 mm; B, not-soft (hard) texture and MPD ≤3 mm; C, soft texture and MPD >3 mm; D, soft texture and MPD ≤3 mm. The classification was evaluated in a multi-institutional, international cohort. - Results: - Of the 2917 articles identified, 108 studies were included in the analyses. Soft pancreatic texture was significantly associated with the development of CR-POPF [odds ratio (OR) 4.24, 95% confidence interval (CI) 3.67-4.89, P < 0.01) following PD. Similarly, MPD diameter ≤3 mm significantly increased CR-POPF risk compared with >3 mm diameter MPDs (OR 3.66, 95% CI 2.62-5.12, P < 0.01). The proposed 4-stage system was confirmed in an independent cohort of 5533 patients with CR-POPF rates of 3.5%, 6.2%, 16.6%, and 23.2% for type A-D, respectively (P < 0.001). - Conclusion: - For future pancreatic surgical outcomes studies, the ISGPS recommends reporting these risk factors according to the proposed classification system for better comparability of results.
Gesehen am 24.04.2023